Two ways for solving a class of rational second-order difference equations - Stevo Stević (Advances in Difference Equations, 2019)
Abstract We consider a class of second-order rational difference equations with two parameters, and we show, in two ways, that the class of equations is solvable in closed form. One way is based on using an invariant for the class of equations, whereas the second one is based on the method of substitution. The main results extend and complement some previous ones in the literature.